THE IMPACT OF FINTECH INVESTMENTS IN TURKEY ON E-COMMERCE - Ataş, Anıl; Kaya, Gamze Ayca (Suat TEKER, 2024)
Purpose- In this study, the diversity and development of fintech investments in the world and in Turkey were examined. Since financial technology investments are fintech investments developed specifically for the e-commerce system, the impact of fintech companies established in Turkey and the investments of currently operating companies on e-commerce were investigated. Methodology- The data set of the study was created with the market share data, sales volumes and number of users of the e-commerce sector between 2019-2023, the data are obtained from the Republic of Turkey. Presidential Finance Office and T.R. It was obtained from the websites of the Ministry of Commerce and analyzed with the SPSS 22 program and regression analysis was applied. Findings- The analysis model shows that the effect of the independent variable on the dependent variable is not significant. Conclusion- Analysis results show that fintech investments alone are not sufficient for the development of e-commerce. It is thought that this research will contribute to researches who will conduct research on a similar subject.

Amaç- Bu çalışmada, Dünyadaki ve Türkiye’deki fintek yatırımlarının çeşitliliği ve gelişimi incelenmiştir. Finansal teknoloji yatırımlarının, özellikle e-ticaret sistemine yönelik geliştirilen fintek yatırımları olması sebebiyle, Türkiye’de kurulan fintek şirketleri ve hâlihazırda faaliyet gösteren şirketlerin yatırımlarının e-ticarete etkisi araştırılmıştır. Çalışmanın amacı, fintek yatırımlarının e-ticaret üzerindeki etkisinin belirlenmesidir. Yöntem- Çalışmanın veri seti, 2019 - 2023 yılları arasındaki e-ticaret sektörünün pazar payı verileri, satış hacimleri ve kullanıcı sayıları ile oluşturulmuş, veriler T.C. Cumhurbaşkanlığı Finans Ofisi ve T.C. Ticaret Bakanlığı’nın internet sitelerinden elde edilerek SPSS 22 programı ile analiz edilmiş ve regresyon analizi uygulanmıştır. Bulgular- Araştırmada, fintek yatırım tutarının (bağımsız değişken) e-ticaret satış hacmi (bağımlı değişken) üzerinde anlamlı bir etkisinin olmadığı belirlenmiştir. Sonuç- Analiz sonuçları, e-ticaretin gelişmesinde fintek yatırımlarının tek başına yeterli olmadığını göstermektedir. Bu araştırmanın, benzer konuda araştırma yapacak araştırmacılara katkı sağlayacağı düşünülmektedir.
TÜRKİYE’DEKİ FİNTEK YATIRIMLARININ E-TİCARETE ETKİSİ
Keywords: Labor Economics; Çalışma Ekonomisi; Microeconomics (Other); Mikro İktisat (Diğer); Finance; Finans; Business Administration; İşletme